ALDH2 Deficiency Promotes Ethanol‐Induced Gut Barrier Dysfunction and Fatty Liver in Mice. (14th July 2015) - Chaudhry, Kamaljit K.; Samak, Geetha; Shukla, Pradeep K.; Mir, Hina; Gangwar, Ruchika; Manda, Bhargavi; Isse, Toyohi; Kawamoto, Toshihiro; Salaspuro, Mikko; Kaihovaara, Pertti; Dietrich, Paula; Dragatsis, Ioannis; et al.
<x xml:space="preserve">Abstract</x> Background Acetaldehyde, the toxic ethanol (EtOH) metabolite, disrupts intestinal epithelial barrier function. Aldehyde dehydrogenase (ALDH) detoxifies acetaldehyde into acetate. Subpopulations of Asians and Native Americans show polymorphism with loss‐of‐function mutations in ALDH2. We evaluated the effect of ALDH2 deficiency on EtOH‐induced disruption of intestinal epithelial tight junctions and adherens junctions, gut barrier dysfunction, and liver injury. Methods Wild‐type and ALDH2‐deficient mice were fed EtOH (1 to 6%) in Lieber–DeCarli diet for 4 weeks. Gut permeability in vivo was measured by plasma‐to‐luminal flux of FITC‐inulin, tight junction and adherens junction integrity was analyzed by confocal microscopy, and liver injury was assessed by the analysis of plasma transaminase activity, histopathology, and liver triglyceride. Results EtOH feeding elevated colonic mucosal acetaldehyde, which was significantly greater in ALDH2‐deficient mice. ALDH2−/− mice showed a drastic reduction in the EtOH diet intake. Therefore, this study was continued only in wild‐type and ALDH2+/− mice. EtOH feeding elevated mucosal inulin permeability in distal colon, but not in proximal colon, ileum, or jejunum of wild‐type mice. In ALDH2+/− mice, EtOH‐induced inulin permeability in distal colon was not only higher than that in wild‐type mice, but inulin permeability was also elevated in the proximal colon, ileum, and jejunum. Greater inulin permeability in distal colon of ALDH2+/− mice was associated with a more severe redistribution of tight junction and adherens junction proteins from the intercellular junctions. In ALDH2+/− mice, but not in wild‐type mice, EtOH feeding caused a loss of junctional distribution of tight junction and adherens junction proteins in the ileum. Histopathology, plasma transaminases, and liver triglyceride analyses showed that EtOH‐induced liver damage was significantly greater in ALDH2+/− mice compared to wild‐type mice. Conclusions These data demonstrate that ALDH2 deficiency enhances EtOH‐induced disruption of intestinal epithelial tight junctions, barrier dysfunction, and liver damage.